A Quantitative Approach to the Study of Deviant Usage of Mood and Modality in Argumentative Essays of Second Year Students of Berekum College of Education - Christopher Gyau (European Scientific Journal, ESJ, 2022)
The aim of the study was to find out the quantitative approach to the study of deviant usages of mood and modality in argumentative essays of second year students of Berekum College of Education in the Ashanti region of Ghana. The main objectives of the study were to investigate the causes of Berekum College of Education students’ inability to use mood and modality features appropriately to write good argumentative essays, identify the specific challenges the students are confronted with and the main causes of their lack of interest for argumentative essays. Data were collected from a purposive sample of 150 second year students of Berekum College of Education by way of questionnaires, an in-class essay test, summary test and objective test. These were analysed using Statistical Package for Social Sciences (SPSS). The findings reveal that there was no exposure to the appropriate use of mood and modality as well as argumentative essays at the pre-college level of their education. The findings also indicate that students were simply of the view that their tutors must serve as role models in the use of the features of mood and modality in all their discussions and deliberations to enable students learn the practicalities of the usage of the concepts from them. It also discloses that second-year students of Berekum College of Education lack interest in writing argumentative essays, and are unable to make appropriate use of mood and modality to be successful in the writing of such essays. It is therefore recommended that students should practise the concepts they are taught to enhance their understanding of mood and modality and their usage in argumentative essays while English tutors avail themselves for in-service training, workshops and seminars to abreast themselves of new trends of teaching language classes, especially in dealing with mood and modality in argumentative essays.